New species and a new record of the genus Rhyacophila Pictet, 1834 (Insecta:Trichoptera, Rhyacophilidae) from India - Ali, Tabraq; Hussain, Zahid; Raina, Rifat Hussain; Majeed, Aquib; Pandher, Manpreet Singh; Javid, P. M. Osman; Parey, Sajad H. (Zootaxa, 2025)
A new species of the genus Rhyacophila Pictet 1834, Rhyacophila sivaramakrishnani sp. nov. of the Rhyacophila curvata group is described and illustrated from the Northwest Himalaya, India. Also, a new record, Rhyacophila kadphises Schmid 1959 is reported. With this addition, the genus is now represented by 168 valid species in India.